Exposure to the herbicide butachlor activates hepatic stress signals and disturbs lipid metabolism in mice. (November 2021) - Yang, Bijing; Liu, Yingwei; Li, Yangwei; Zhu, Shanshan; Li, Yuanliang; Yi, Jiangnan; Ouyang, Zhuanxu; Liu, Bingxian; Mehmood, Khalid; Hussain, Riaz; Pan, Jiaqiang; Hu, Lianmei; et al.
Abstract: Butachlor is a systemic herbicide widely applied on wheat, rice, beans, and different other crops, and is frequently detected in groundwater, surface water, and soil. Therefore, it is necessary to investigate the potential adverse health risks and the underlying mechanisms of hepatotoxicity caused by exposure to butachlor in invertebrates, other nontarget animals, and public health. For this reason, a total of 20 mice were obtained and randomly divided into two groups. The experimental mice in one group were exposed to butachlor (8 mg/kg) and the mice in control group received normal saline. The liver tissues were obtained from each mice at day 21 of the trial. Results indicated that exposure to butachlor induced hepatotoxicity in terms of swelling of hepatocyte, disorders in the arrangement of hepatic cells, increased concentrations of different serum enzymes such as alkaline phosphate (ALP) and aspartate aminotransferase (AST). The results on the mechanisms of liver toxicity indicated that butachlor induced overexpression of Apaf-1, Bax, Caspase-3, Caspase-9, Cyt-c, p53, Beclin-1, ATG-5, and LC3, whereas decreases the expression of Bcl-2 and p62 suggesting abnormal processes of apoptosis and autophagy. Results on different metabolites (61 differential metabolites) revealed upregulation of PE and LysoPC, whereas downregulation of SM caused by butachlor exposure in mice led to the disruption of glycerophospholipids and lipid metabolism in the liver. The results of our experimental research indicated that butachlor induces hepatotoxic effects through disruption of lipid metabolism, abnormal mechanisms of autophagy, and apoptosis that provides new insights into the elucidation of the mechanisms of hepatotoxicity in mice induced by butachlor. Graphical abstract: Image 1 Highlights: Exposure to the herbicide butachlor results in hepatotoxicity. Butachlor exposure induced apoptosis and autophagy in hepatocytes. Butachlor significantly altered the variation of 61 metabolites and disturbed lipid metabolism. PE and LysoPC disturbed the glycerophospholipid metabolism under butachlor exposure.